Effect of Time after Mating on the Recovery and Motility of Spermatozoa from the Female Reproductive Tract of Ewes - Ismaya, Ismaya (2014)
The aim of the study was to determine the effect of time after mating on the recovery and motility of spermatozoa in the reproductive tract of Merino ewes. After natural mating, ewe was necessary to kill to obtain samples with the reproductive tract of ewes was removed. Samples of fluid and mucus from various sites in the reproductive tract of ewes were collected into tyroid’s albumin-lactate-pyruvate (TALP) medium at 1, 3, 6 and 24 hours after mating for determination of recovery and motility of spermatozoa by computer aided semen analyser (CASA). Data were analysed using SPSS software program. Analysis of variance one way classification was used to determine the effect of time after mating on the recovery and motility of spermatozoa in the reproductive tract of ewes (in vivo). Results study showed that the number of spermatozoa in the vagina, cervix, uterus and oviduct decreased significantly (P<0.05) with time after mating. At 6 and 24 hours, the mean number of spermatozoa recovered from the right isthmus and right ampulla were 400 ± 25, 200 ± 50 and 140 ± 15, 130 ± 25, respectively. At 24 hours after mating the percentage of motile, progressively motile and rapidly motile spermatozoa in all the sites of the reproductive tract was very low and was not significantly different. In conclusion, the number of spermatozoa recovered and motility was influenced by the time after mating and the site of the reproductive tract of ewes.